IMPACT OF POST-BREEDING HORMONAL TREATMENT ON CONCEPTION IN REPEAT BREEDING GIR CATTLE AT A GAUSHALA - PARMAR, S V; PATEL, J A; DHAMI, A J; SHAH, R G (The Indian Journal of Animal Reproduction, 2016)
Repeat breeding Gir cattle (n=24) of a Gaushala were randomly and equally allotted to buserelin group (postbreeding 0.02 mg buserelin acetate, i.m.), hCG group (post-breeding 1500 IU hCG, i.m.), progesterone group (Day 6 post-breeding 500 mg hydroxyl progesterone caproate, i.m.) and control (no hormonal treatment). The overall conception rate (till cycle II post-treatment) of hormonal treatment groups was higher compared to controls (72.2 vs 33.3%, p<0.05). Plasma progesterone in cattle that conceived subsequently had a consistently increasing trend till week 6 post-treatment. Plasma total protein, total cholesterol and triglycerides were similar (p>0.05) between treatment groups as well as between conceived and non-conceived counterparts. This study indicated beneficial role of the use of hormone therapy for improving conception rate in repeat breeding Gir cattle at Gaushalas.